Dor aguda no pós-operatório de craniotomia eletiva : características e manejo do fenômeno doloroso - Ribeiro, Maria do Carmo de Oliveira (2012)
Introduction: pain is a symptom that commonly occurs in post-operative craniotomy, which compromises the neurological evaluation and surgical recovery. Objectives: identify the acute pain in the craniotomy postoperative period in relation to variables: location, intensity, duration and aggravating factors; examine the pain register carried out by the health team; check the prevalence of pain during the first week after craniotomy and its consequences and characterize the factors involved in the occurrence of postoperative pain. Material and Method: this is an observational, longitudinal study with a quantitative approach. Developed in the Intensive Care Unit and department of Neurosurgery at the Foundation of Beneficência Hospital of Surgery, Aracaju/IF. The sample was probabilistic, consecutive convenience, consisted of 100 patients undergoing elective craniotomy. Data collection occurred from September 2010 until October 2011. The variables analyzed were gender, age, medical history, indication of craniotomy, type of surgery, headache occurrence, register of pain in medical records, hospital stay, aggravating factors, intensity, consequences of pain and analgesic use. Systematic data collection occurred through the selection of records followed by analysis and interviews with patients undergoing craniotomy. These patients were evaluated from the first to the eighth postoperative day and/or until hospital discharge. A multiple logistic regression model was developed to determine the factors that could explain the presence of postoperative pain. The Chi-square test, Fisher's Exact Test and paired t-test were used. In the whole study a statistical significance level of 5 % was adopted. Results the data demonstrated that 59% were female, with an average age of 44.6 ± 14.5 years and 57% were single. In 55% of cases, the diagnosis was a brain tumor, and 36% cerebral aneurysm. Headache was the main pain complaint, characterized as moderate, and its prevalence was 24.2 % in the 1st postoperative day (POD). The pain was mostly continuous type in 76.3% of patients and the bed position was the aggravating factor of the painful phenomenon in 10.9% of the cases. It was found that in 71%of the cases there was no record of pain by the health team. The pain consequences reported by patients were: insomnia, the ability to cough and decreased appetite, and impaired ambulation. It was found that the analgesics used were the non-steroidal anti-inflammatory in 75% of the cases and that they were not sufficient for the pain relief, with a view that in 22% of patients, the pain remained after analgesia. The final logistic regression model indicated that the age < 45 years (OR=3.0, p=0,041 ) and the time of surgery > 4 hours (OR=3.7, p=0.019) were predictive factors for the occurrence of headache immediately after the craniotomy. Conclusion: the data show that prevalent pain was the headache, characterized as moderate, continuous type, the painkillers were not effective for the pain relief and that there was a underreporting of the pain phenomenon. The main pain consequence was insomnia. The age < 45 years and surgery time > 4 hours are associated with the occurrence of post-surgery headache.